2004
DOI: 10.1099/ijs.0.02908-0
|View full text |Cite
|
Sign up to set email alerts
|

Vagococcus carniphilus sp. nov., isolated from ground beef

Abstract: Nine enterococcus-like strains were referred to the Streptococcus Laboratory at the Centers for Disease Control and Prevention (CDC) for further identification from the National Antimicrobial Resistance Monitoring System Laboratory at the CDC. The cultures were isolated from ground beef purchased from retail in Oregon in 2000. Conventional biochemical testing and analysis of whole-cell protein electrophoretic profiles distinguished these strains from known species of enterococci and vagococci. Comparative 16S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 24 publications
(14 reference statements)
2
27
0
Order By: Relevance
“…Amplification and sequencing of the 16S rRNA gene were performed as previously described (25,26). Sequencing reaction products were purified with Centri-Sep plates (Princeton Separations, Princeton, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…Amplification and sequencing of the 16S rRNA gene were performed as previously described (25,26). Sequencing reaction products were purified with Centri-Sep plates (Princeton Separations, Princeton, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…Some could be characterized as Enterococcus casseliflavus and Enterococcus gallinarum by sodA gene sequences only (Fig. 3), whereas 16S rRNA analysis eventually revealed several others to be Vagococcus fluvialis or Vagococcus carniphilus, a species recently reported to be in beef meat (39). This was the only case, indeed, in which ARDRA did not enable the assignment of isolates to the correct genus.…”
Section: Resultsmentioning
confidence: 88%
“…3). Vagococcus carniphilus from ground beef was previously isolated and described by Shewmaker et al (2004). It was observed that the organism could grow in the presence of 6.5% NaCl.…”
Section: Identification Of the Isolatementioning
confidence: 99%
“…Isolate identification was carried out according to Bergey's Manual of Systematic Bacteriology (Krieg and Holt 1984) and by comparing with standard culture described earlier (Shewmaker et al 2004) on the basis of morphological, biochemical and physiological tests, and further confirmed by 16S rDNA sequencing. Morphological studies were carried out by microscopic observations of Gram stained cells under an oil immersion objective on a light microscope and scanning electron microscopy (SEM) using a previously described procedure (Joshi et al 2007).…”
Section: Identification and 16s Rdna Sequencingmentioning
confidence: 99%